Socialization and inclusion of students in physical education classes through the chess game - Huianu Elena-Adriana; Florin LEUCIUC (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
For children, the game of chess is quite important, as it helps them to become responsible human beings, with a fairly high degree of discipline and much wiser. By associating chess with the physical activity in physical education classes, we offer children all the leverage for healthy development. The purpose of the present paper is to highlight the fact that practicing chess at any school age contributes to the fulfillment of the functions of physical education and becomes a means of socialization. The game of chess used in physical education classes and during school breaks was aimed at socializing students. The students included in the present research were tested by applying the items of the questionnaire. The school planning elaboration of the chess course is designed according to the age of the students and taking into account their ability to concentrate. The organization of the class of students is in pairs and groups, having the game of chess as a means of work.